2016
DOI: 10.1175/jamc-d-15-0075.1
|View full text |Cite
|
Sign up to set email alerts
|

The Extrapolation of Near-Surface Wind Speeds under Stable Stratification Using an Equilibrium-Based Single-Column Model Approach

Abstract: Classical approaches to modeling the near-surface (i.e., below 200 m) wind profile are equilibrium based (i.e., no time evolution) and either lack a physical basis or are based on surface-layer physics. In this study, the limits of the equilibrium approach in stable stratification are further tested by applying the method within a more physically comprehensive single-column model (SCM) framework. The SCM considered here is a highly idealized momentum and temperature budget model that uses a range of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…where K m and K h are the eddy diffusivities for momentum and temperature, respectively. These terms are themselves parameterized with a range of possible options in the literature (Optis andMonahan, 2016, 2017). We adopt a relatively simple first-order closure model that includes eddy diffusivities that are related to the wind speed gradient and a stability function that depends on the Richardson number:…”
Section: Single-column Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…where K m and K h are the eddy diffusivities for momentum and temperature, respectively. These terms are themselves parameterized with a range of possible options in the literature (Optis andMonahan, 2016, 2017). We adopt a relatively simple first-order closure model that includes eddy diffusivities that are related to the wind speed gradient and a stability function that depends on the Richardson number:…”
Section: Single-column Modelmentioning
confidence: 99%
“…There are a range of proposed formulations for the mixing lengths and stability functions. Here, we use the one developed by Smith (1990), which showed strong results when used in an SCM in previous studies (Optis andMonahan, 2016, 2017). A detailed explanation and the equations of the stability functions and mixing lengths can be found in Smith (1990), Cuxart et al (2006), and Optis and Monahan (2017).…”
Section: Single-column Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Such models are flexible in determining which processes and parameterizations are included (e.g., turbulence, radiation, entrainment, land surface characteristics, etc. ), allow for the specification of lower boundaries above the surface (Optis and Monahan 2016), and generally have low computational requirements. Models range in complexity from those that incorporate detailed physics (similar to a 3D model) to idealized representations that may only consider the budget equations (e.g., momentum and temperature).…”
Section: Introductionmentioning
confidence: 99%
“…and relationships between parameters (e.g., flux-gradient relationships) can then be evaluated from the quasi-equilibrium state. This approach has been used in a number of studies to explore SBL characteristics (e.g., Weng and Taylor 2006;Sterk et al 2013;Sorbjan 2012Sorbjan , 2014 and to compare different turbulence parameterizations (e.g., Weng and Taylor 2003;Cuxart et al 2006;Edwards et al 2006;Optis and Monahan 2016). In a previous study, we identified several limitations of the equilibrium approach (Optis and Monahan 2016).…”
Section: Introductionmentioning
confidence: 99%